ANALYSIS OF DIALOGUE TECHNIQUE ACCEPTANCE OF DIAGNOSIS BASED CLINICAL DECISION SUPPORT SYSTEM - Sulistianingsih N.; Kusumadewi S.; Kariyam Kariyam (Universitas Trunojoyo Madura, 2015)
Many decision support systems have been developed to diagnose diseases, but in reality many of these systems fail when applied. This is mainly due to the difficulties in the use of the system due to incompatibility between the system interface and the wishes of physicians. The purpose of this study was to determine the interface design of decision support systems for diseases diagnose in accordance with physician’s wishes and to determine the effects of perceived usefulness and perceived ease of use on the behavioral intention to use the interface design. The data analysis technique used included the Wilcoxon test, the Friedman test, a principal component analysis and a multiple linear regression analysis. From the data analysis it was found that in anamneses and physical examinations, respondents prefer the interface design of natural language processing and a form filling dialogue, whereas in supported examinations, respondents prefer windowing system interface designs. Advanced data analyses found an influence of the variables of perceived usefulness and perceived ease of use on the behavioral intention to use and this influence has a positive effect.